PENINGKATAN KEDISIPLINAN SISWA MELALUI SISTEM KREDIT POIN OLEH SDU (SMADA DISCIPLINE UP HOLDER) DI SMA NEGERI 2 NGAWI - Prasetyo, Denny Adi (Prodi PPKn FKIP UNS, 2013)
The purpose?s of research are: 1) to investigate the implementation of the credit points system by the SDU in improving student?s discipline attitude at SMAN 2 Ngawi; 2) to know the impact of the system credit point?s implementation by the SDU about the student?s discipline attitude in SMAN 2 Ngawi.This research used a qualitative approach with descriptive research form. The source of data that be used consist of: informants, observation sheet and document analysis sheet. The sampling technique that be used was aims samples (purposive sampling). The technique of collecting data through interview, observation and documentation. The validity of the data by using a triangulation of data or sources. The data analysis technique that be used was interactive analysis model which consists of four major components, namely data collection, data reduction, data presentation and conclusion.The results indicated that the implementation of the credit points system by SDU was implemented through three programs: 1) keeping the gate operation was carried out every day at 6:00 am to 7:00 am except during mid semester or semester test, 2) class raid is conducted between the two times up to four times a month, 3) operation before the flag ceremony every Monday. There are form of attitude that be showed by the students of SMAN 2 Ngawi had been embedded discipline character include: 1) most of students don?t come late to school, 2) most of students complete the attributes and school uniforms; 3) following the school teaching , did not make some noises during school hours , no ditching, 4) always follow the flag ceremony except during illness; 5) did not carry unnecessary items to school, 6) did not streak benches and walls; 7) keeping the school cleaning.